1999
DOI: 10.1007/s003920050276
|View full text |Cite
|
Sign up to set email alerts
|

Die medikamentöse Prophylaxe nach elektronischer Kardioversion von chronischem Vorhofflimmern

Abstract: Atrial fibrillation (AF) is the most frequent cardiac arrhythmia. However, despite manifold publications reflecting numerous clinical trials about treatment of AF, the management of this arrhythmia is still under controversial discussion, in daily clinical work as well as in research. The present study concentrates on three major questions: 1. How frequent are recurrences of AF in long-term follow-up? Most of the previous studies used the occurrence of symptoms as a surrogate parameter for recurrences of AF, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
5
0
4
Order By: Relevance
“…Auch bei ihnen besteht jedoch eine schlechte Korrelation zwischen dem Auftreten oder Bestehen der Rhythmusstörung und Symptomen [18]. In der PAFAC-Studie (nach Kardioversion tägliches Tele-EKG) bemerkten 70% der Patienten die Rezidive nicht [19].…”
Section: Klinisches Bild Bei Vorhofflimmernunclassified
See 1 more Smart Citation
“…Auch bei ihnen besteht jedoch eine schlechte Korrelation zwischen dem Auftreten oder Bestehen der Rhythmusstörung und Symptomen [18]. In der PAFAC-Studie (nach Kardioversion tägliches Tele-EKG) bemerkten 70% der Patienten die Rezidive nicht [19].…”
Section: Klinisches Bild Bei Vorhofflimmernunclassified
“…Ausschlusskriterien ab; so erlaubte z.B. die PAFACStudie [19] korrigierte QT-Zeiten unter Sotalol von bis zu 0,54 s und musste 2,3% TdPTachykardien in Kauf nehmen [55].…”
Section: Hämodynamische Effekte Von Vorhofflimmernunclassified
“…In addition, the main goal of treatment in atrial fibrillation is to reduce symptomatic episodes, since it has never been shown that atrial stabilization, for example, decreases the risk of stroke. The importance of this statement is supported, for example, by the German Prevention of Atrial Fibrillation After Cardioversion (PAFAC) study [25,26] that compared the combination of quinidine and verapamil with (+/−)-sotalol to maintain sinus rhythm. In this study daily transtelephonic monitoring showed that more than 80% of atrial fibrillation episodes were asymptomatic.…”
Section: Maintenance Of Sinus Rhythmmentioning
confidence: 99%
“…Bei einer Auswertbarkeit der übertragenen EKG von 95% betrug die Inzidenz von Vorhofflimmern bei 120 000 Übertragungen 3,3%. In 75,4% der dokumentierten Episoden traten diese ohne begleitende Symptome auf [14].…”
Section: Epidemiologieunclassified